APLIKASI PACLOBUTRAZOL TERHADAP PERTUMBUHAN DAN PRODUKSI PADA TANAMAN TOMAT (Licopersicum esculentum Mill.) - Rivaldi Moko; Saartje Sompotan; Paula C. H. Supit (COCOS, 2018)
ABSTRACT This study aims to study the effect of paclobutrazol on the growth and production of tomato plants. The research was conducted at the Experimental Garden of the Pandu Agricultural Technology Assessment Center in Talawaan Bantik Village, Wori District, North Minahasa Regency. Starting from September 2017 and ending in January 2018. This study used a randomized block design consisting of 6 levels of paclobutazol concentrations of 0 ppm, 75 ppm, 100 ppm, 125 ppm, 150 ppm, 175 ppm. Variables were observed for plant height, time / time of flowering (days after seeding), number of crop collections, and fruit weight. The use of paclobutrazol in tomato plants has a significant influence on plant height at flowering and number of leaves. The administration of paclobutrazol with a concentration of 125 ppm gave the greatest emphasis which produced the lowest plant height of 47.75 cm.Â  The use of paclobutrazol in tomato plants can delay the flowering process compared to without using paclobutrazol. The effect of paclobutrazol on flowering is a secondary influence, while the primary effect is suppression of vegetative growth. Keywords: Application of Paclobutrazol in Tomato Plants